The Magic of Forgery: Patterns of Distraction in the Authentication of Suspicious Objects - Klawans, Jonathan (Journal of ancient Judaism, 2023)
This article surveys and categorizes problematic arguments that recur in academic authentications of suspicious objects, especially biblically-related forgery cases (often arising from antiquities markets). Academic authenticators are often attracted to the “allure of significance” promised by unprovenanced objects purportedly related to biblical people or places. Authentication often displays a “cooption of creativity”: freely imaginative reconstructions of ancient origins are propped up by preclusions of the possibility of forgery. Combining these two moves into a third, authenticators spin inconsistencies to their advantage, arguing that what is unparalleled in the suspicious object provides evidence of new, important, unattested phenomena. Authenticators highlight the “drama of discovery,” even if the drama must be invented. Finally, authenticators slip into the language and legalities of crime-solving: if an alleged forger cannot be proven guilty, then the object should be considered authentic. Such arguments appear in failed authentications of the past, resurfacing in present controversies.